THE INTENSITY OF SCATTERING OF CHARGE CARRIERS IN GRAPHENE, LOCATED ON A SUBSTRATE OF HEXAGONAL BORON NITRIDE - V. V. Muraviev; V. N. Mishchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of modeling the scattering intensities of charge carriers in graphene located on a substrate of hexagonal boron nitride are presented. Graphene is considered a promising material for the formation of new semiconductor devices with good characteristics for the microwave and HF bands. Formulas are presented that allow modeling of the main electron scattering intensities in a single layer of graphene placed on a substrate of boron nitride. The dependences of the scattering intensity on optical phonons associated with the interface between graphene and a layer of hexagonal boron nitride are obtained when the thickness of the gap between these layers changes. Simulation of fixed rate dispersion was carried out as for normal temperature equal to 300 K and at elevated – equal to 370, which is connected with the necessity of considering the temperature rise of the graphene layer with increasing electron energy. The analysis of the obtained dependences showed that at electron energy values that exceed a value equal to approximately 0.165 eV, there is a predominance of electron scattering on optical phonons inherent in the inner layer of graphene, electron-electron scattering, as well as scattering on optical phonons associated with the interface between graphene and a layer of hexagonal boron nitride, over other types of scattering. At low energy values, which are less than about 0.03 eV, the dispersion on impurities prevails over other types of dispersion. Based on the obtained dependences of electron scattering intensities in graphene, it becomes possible to implement the Monte – Carlo statistical method to determine the characteristics of electron transfer in semiconductor devices containing layers of graphene and hexagonal boron.